TITRIMETRIC ANALYSIS OF IBUPROFEN BULK DRUG SAMPLE BY USING UREA AS A HYDROTROPIC SOLUBILIZING AGENT - A., Pol Pradnya; P., Mehta Preeti (International Journal of Current Pharmaceutical Research, 2015)
Objective: The objective of this study was to employ hydrotropic solublization technique to facilitate the tirimetric analysis of poorly water soluble drug, ibuprofen precluding the use organic solvent. Methods: In the present investigation, poorly water-soluble anti-inflammatory drug, ibuprofen has been solubilized using 8M of urea as hydrotropic agent for its titrimetric analysis instead of using organic solvent. Results: There was an enhancement in solubility of ibuprofen in 8M urea solution as compared to solubility in distilled water. The mean percent estimation of ibuprofen estimated in bulk sample by Indian Pharmacopoeial Method is 98.56% while by the proposed method (using 8M urea) is 98.67%. The results of analysis by the proposed method are very close to the results of the standard method. Conclusion: Proposed method is simple, economic, accurate, eco-friendly and can be successfully employed in the routine quantitative analysis of drug in bulk drug and dosage form in industries.